Can a Village Website Be an Indicator of Public Transparency? - Mika Puspitasari; Choironi Ardiyansyah; Aprina Nugrahesthy Sulistya Hapsari (Asia Pacific Fraud Journal, 2023)
The village is the lowest unit that must be a government structure which in financial management is based on the principles of good governance and transparency. Transparency as accountability to all stakeholders as well as a supervisory effort to minimize fraudulent forms of financial management. One form of transparency is through the management of village websites. But in reality the village website has not been managed optimally. Therefore, this study aims to analyze the transparency of village financial management through websites in 280 villages that are within the scope of the Grobogan Regency area. The method used is qualitative research with a descriptive interpretation approach, namely observing, describing and interpreting objects and then drawing conclusions. Data collection based on content analysis regarding village management achievements. The results showed that the utilization of village websites in Grobogan Regency as a form of transparency had not been maximized. The lack of transparency is due to the lack of information provided, and many websites only provide tools with no content in them, thereby triggering a possible decrease in public and other stakeholders’ trust in village management